Sleep duration, vital exhaustion, and odds of spontaneous preterm birth: a case–control study - Sánchez, Sixto E. (2014)
Background Preterm birth is a leading cause of perinatal morbidity and mortality worldwide, resulting in a pressing need to identify risk factors leading to effective interventions. Limited evidence suggests potential relationships between maternal sleep or vital exhaustion and preterm birth, yet the literature is generally inconclusive. Methods We examined the relationship between maternal sleep duration and vital exhaustion in the first six months of pregnancy and spontaneous (non-medically indicated) preterm birth among 479 Peruvian women who delivered a preterm singleton infant (<37 weeks gestation) and 480 term controls who delivered a singleton infant at term (≥37 weeks gestation). Maternal nightly sleep and reports of vital exhaustion were ascertained through in-person interviews. Spontaneous preterm birth cases were further categorized as those following either spontaneous preterm labor or preterm premature rupture of membranes. In addition, cases were categorized as very (<32 weeks), moderate (32–33 weeks), and late (34- <37 weeks) preterm birth for additional analyses. Logistic regression was used to estimate adjusted odds ratios (aORs) and 95% confidence intervals (CIs). Results After adjusting for confounders, we found that short sleep duration (≤6 hours) was significantly associated with preterm birth (aOR = 1.56; 95% CI 1.11-2.19) compared to 7–8 hours of sleep. Vital exhaustion was also associated with increased odds of preterm birth (aOR = 2.41; 95% CI 1.79-3.23) compared to no exhaustion (Ptrend <0.001). These associations remained significant for spontaneous preterm labor and preterm premature rupture of membranes. We also found evidence of joint effects of sleep duration and vital exhaustion on the odds of spontaneous preterm birth. Conclusions The results of this case–control study suggest maternal sleep duration, particularly short sleep duration, and vital exhaustion may be risk factors for spontaneous preterm birth. These findings call for increased clinical attention to maternal sleep and the study of potential intervention strategies to improve sleep in early pregnancy with the aim of decreasing risk of preterm birth.